Diagnóstico da produção de arroz na Aldeia Cuor, na Guiné Bissau: desafios e perspectivas - Silla, Issufi (2024)
The aim of the work was to carry out a diagnosis of the current situation of rice production in the Cuor village, in Bambadinca, Guinea-Bissau, seeking to identify the main threats faced and propose a management strategy to improve its cultivation. Rice production is crucial to the country's food security and economy, representing one of its main cultivated species. Interviews with farmers revealed the challenges faced, the agricultural practices adopted and perceptions about the future of farming. The majority of farmers come from rural families, which reinforces the village's agricultural tradition. Despite its strong connection to agriculture, many are moving to urban areas in search of better economic opportunities. The research identified that most farmers use cultivation practices in flooded floodplains, and some adopt the rainfed system. Rice cultivation, deeply rooted in local traditions, is based on ancestral knowledge, with a history of cultivation dating back millennia. The use of fire to clear cultivated areas is common, although its long-term negative impacts are worrying. The relationship between traditional and scientific knowledge is predominant, resulting in improvements in rice production and quality. However, economic barriers limit access to inputs and technologies. The research also indicated that productivity varies depending on the cultivation system, being lower in rainfed areas and higher in freshwater floodplains. The Balanta, Fula and Mandinga ethnic groups are mainly responsible for rice production, each contributing in a different way, depending on the region and the system adopted. This study also evaluated the impact of salinity on the emergence of rice seeds in this location, with the aim of offering alternatives to recover salinized areas. The experiment was carried out in hydromorphic soil with low drainage and high salinity characteristics. Two plots of 10 m² were prepared, one with the addition of organic matter and the other without, to serve as a control. Organic matter was incorporated into the surface horizon of the soil, facilitating drainage and reducing salt concentration over 50 days. The results indicated that organic matter decreased salinity in the surface layer and increased the emergence rate of rice seeds, while in the control plot emergence was very low. The study concluded that the use of organic fertilizer improves the structure and water retention capacity of the soil, promoting the leaching of salts and favoring plant growth. These practices can help in the recovery of agricultural areas affected by salinization, contributing to the sustainability of local agriculture and food security in regions with naturally salinized soils. Rice production faces several challenges, and integrated strategies are essential to increase the productivity and sustainability of the sector.